IEEE International Conference on Mobile Adhoc and Sensor Systems Conference, 2005.
DOI: 10.1109/mahss.2005.1542812
|View full text |Cite
|
Sign up to set email alerts
|

Sensor networks deployment using flip-based sensors

Abstract: In this paper, we study the issue of mobility based sensor networks deployment. The distinguishing feature of our work is that the sensors in our model have limited mobilities. More specifically, the mobility in the sensors we consider is restricted to a flip, where the distance of the flip is bounded. Given an initial deployment of sensors in a field, our problem is to determine a movement plan for the sensors in order to maximize the sensor network coverage, and minimize the number of flips. We propose a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
(25 reference statements)
0
47
0
1
Order By: Relevance
“…Chellappan et al [3] presented a centralized algorithm for mobility-limited sensors. They divide the target field into weighted regions and model the sensor self-deployment problem as a minimum-cost maximum-flow problem.…”
Section: Related Workmentioning
confidence: 99%
“…Chellappan et al [3] presented a centralized algorithm for mobility-limited sensors. They divide the target field into weighted regions and model the sensor self-deployment problem as a minimum-cost maximum-flow problem.…”
Section: Related Workmentioning
confidence: 99%
“…We have implemented the DCC concept to solve the autonomous sensor deployment problem 1 . DCC consists of 3 major stages: planning, computing, and moving.…”
Section: Dynamic Cooperative Coevolution Frameworkmentioning
confidence: 99%
“…Chellappan et al [1] proposed a flip-based algorithm to optimize both the coverage and the total number of flips. More recently, it has been demonstrated that computational intelligence techniques, such as fuzzy logic [8] and swarm intelligence [12] can be effective in sensor deployment.…”
Section: Introductionmentioning
confidence: 99%
“…One is the most commonly used binary sensor model [1,2,[4][5][6][7][8][9][10]. In this model, a sensor detects with probability 1 (resp., 0) the target events happening inside (resp., outside) its sensing range, a disc centered at itself.…”
Section: Sensing Range Diminishmentmentioning
confidence: 99%
“…There are two main streams of algorithms, i.e., sensor self-deployment [1][2][3][4][5][6][7] and sensor relocation [8][9][10], for coverage improvement in MSNs. Other streams include, for example, robot-assisted approaches [11,12].…”
Section: Introductionmentioning
confidence: 99%